Laboratory analogue of a supersonic accretion column in a binary star system - J. E. Cross (Nature Portfolio, 2016)
Stationary radiative shocks are expected to form above the surface of highly-magnetized white dwarves in binary systems, but this cannot be resolved by telescopes. Here, the authors report a laboratory experiment showing the evolution of a reverse shock when both ionization and radiative losses are important.